Systematic Literature Review: Implementation of a Problem-Based Learning Model with Ethnomathematics Nuances in Improving Students' Mathematical Problem Solving Ability - Maharani, Laila Amay; Waluya, Stevanus Budi (Indonesian Journal Publisher, 2024)
The industrial revolution in the 21st century brought changes to the education system, especially in terms of learning media, where the media used must implement the results of innovation. For example, ethnomathematics is used to increase students' competence in finding solutions to mathematical problems. The aim of carrying out this research is to analyze the extent of students' abilities in solving mathematical problems after receiving based learning Problem Based Learning with ethnomathematics methods. Meanwhile, the research implementation method implements SLR (Systematic Literature Review) by reviewing several articles that have similar topics in the form of developing student competence in solving mathematical problems based on ethnomathematics in the Problem Based Learning learning modeland published between 2019 and 2023. The number of national and international articles used as literature studies was 13 articles. This article was obtained by researchers from the Google Scholar publish or perish database. Based on the analysis carried out, the results showed that the effectiveness of the ethnomathematics-based Problem Based Learning learning model was found in optimizing student competence in terms of solving mathematical problems.